A Comprehensive Systematic Review of Risk Factor and Management Approach of Gout Arthritis in General Practice - Rini Armaida Purba; Charles Sanjaya Seikka (International Medical Journal Corp. Ltd, 2025)
Background: Gout arthritis is a chronic inflammatory joint disease caused by the accumulation of monosodium urate (MSU) crystals. The main factor that triggers the formation of MSU crystals is high serum uric acid levels (hyperuricemia). This systematic review aims to identify and analyze the risk factors, management, and prevention of gout arthritis based on literature published in the last ten years. Methods: This study followed the PRISMA 2020 standard, examining English-language literature from 2015 to 2025. This study excluded editorials, reviews from the same journal, and submissions without DOI. PubMed, SagePub, SpringerLink, and Google Scholar were used as literature sources. Results: Initially obtaining 360 articles from online databases (PubMed, SagePub, SpringerLink, and Google Scholar), eight relevant papers were selected after three rounds of screening for full-text analysis. Conclusions: Treatment of gouty arthritis is done through a combination of pharmacological therapy and lifestyle changes. Prevention involves managing risk factors such as hypertension, obesity, and alcohol consumption. Education and appropriate long-term treatment can reduce attacks and improve the patient's quality of life.